(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Purpose - The present study was conducted among employees of private sector in Palakkad District, regarding the role of Staff Welfare Club in accentuating Team Work and Organizational Commitment among the employees. It is definite that the various activities conducted by Staff welfare clubs can increase organizational commitment by promoting employee wellbeing and satisfaction. Design / Methodology Approach –This study explores the role of Staff Welfare Clubs (SWC) as a mediating factor in the relationship between Team Work (TW) and Organisational Commitment (OC) among employees working in the private sector. The data were collected from respondents residing and employed within five major municipalities of Palakkad district, Kerala—namely, Palakkad, Ottapalam, Shoranur, Pattambi, and Cherpulassery. These locations were strategically selected due to their urban structure, concentration of private establishments, and diversity in employee profiles. Prior to the main survey, a pilot study was conducted among 65 private sector employees from various industries including finance, education, retail, and healthcare. The objective was to test the clarity, reliability, and relevance of the measurement items. Based on the pilot feedback, minor adjustments were made to wording and formatting of the questionnaire to improve respondent comprehension and consistency. The survey was done both online and offline through company HR departments, employee WhatsApp groups, and professional networking circles. Participants were assured anonymity and confidentiality to encourage honest responses.